Design and Implementation The Learning of Classification Aromatherapy made from Indonesian Spices using K-Nearest Neighbor (KNN) - Maulia Wijiyanti Hidayah; Muhammad Ashar; I Made Wirawan (Journal of Disruptive Learning Innovation (JODLI), 2019)
Indonesia is country that has various plants which have many benefits for human. There are more than 31 types of medicinal plants as one of material that needed by industry as traditional medicine and spices. Traditional spiceal medicine comes from spiceal plants that used from Indonesian spices. This spices can produce aromatherapy include essential oils. Aromatherapy can help in maintaning the healthy of human body. This is necessary that aromatherapy can be classsified using K-Nearest Neighbor to classify aromatherapy from Indonesian spices. The accuracy result which shown by K-Nearest Neighbor algorithm is 97.5 percent, the accuracy data testing using confusion matrix which will be followed by front end and back end testing that shown the valid result for application design and valid using weka application with an accuracy result of 97.5 percent. This research will produce product such as android application that can be accessed by android users.